PERANCANGAN PROGRAM PENJUALAN KECAP PADA PT. KORMA JAYA UTAMA JAKARTA - Nur Aini Setyawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
In the current era of globalization, information technology is advancing rapidly. PT. Korma Jaya Utama requires a computerized system that supports and provides good service for its employees. For this reason, the author tries to make the Design of the Sales Program at PT. Korma Jaya Utama Jakarta. PT. Korma Jaya Utama is a company engaged in the food processing industry, especially soy sauce. The system at PT. Korma Jaya Utama is done semi-computerized, so it has obstacles that often occur such as errors in sales, searching for data that is long enough, recording sales that are still done manually, errors in the calculation of sales so that reports that require a long time. So that with a computerized system this is the best solution to solve the problems that exist in this company, and with a computerized system can be achieved an activity that is effective and efficient in supporting the activities of this company.